2018
DOI: 10.1083/jcb.201711002
|View full text |Cite
|
Sign up to set email alerts
|

Starvation induces rapid degradation of selective autophagy receptors by endosomal microautophagy

Abstract: It is not clear to what extent starvation-induced autophagy affects the proteome on a global scale and whether it is selective. In this study, we report based on quantitative proteomics that cells during the first 4 h of acute starvation elicit lysosomal degradation of up to 2-3% of the proteome. The most significant changes are caused by an immediate autophagic response elicited by shortage of amino acids but executed independently of mechanistic target of rapamycin and macroautophagy. Intriguingly, the autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
220
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(230 citation statements)
references
References 106 publications
(144 reference statements)
9
220
1
Order By: Relevance
“…Moreover, in yeast and very recently in mammalian cells, it has been shown that autophagy induction is highly coordinated with protein sorting and MVE biogenesis. Autophagy receptors such as p62/SQSTM1 or NBR1 are rapidly and selectively targeted to lysosomal degradation by sorting in MVEs in starved cells, which may be a prerequisite to achieve a maximal bulk macroautophagy flux . Note that inhibition of PIKfyve activity, thus impairing MVE fusion with lysosomes, was shown to induce high enrichment of these autophagy receptors in secreted exosomes …”
Section: Similarities Between Degradative and Secretory Mvesmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, in yeast and very recently in mammalian cells, it has been shown that autophagy induction is highly coordinated with protein sorting and MVE biogenesis. Autophagy receptors such as p62/SQSTM1 or NBR1 are rapidly and selectively targeted to lysosomal degradation by sorting in MVEs in starved cells, which may be a prerequisite to achieve a maximal bulk macroautophagy flux . Note that inhibition of PIKfyve activity, thus impairing MVE fusion with lysosomes, was shown to induce high enrichment of these autophagy receptors in secreted exosomes …”
Section: Similarities Between Degradative and Secretory Mvesmentioning
confidence: 98%
“…Conversely, ESCRT components have been shown to be involved in autophagy . Moreover, in yeast and very recently in mammalian cells, it has been shown that autophagy induction is highly coordinated with protein sorting and MVE biogenesis. Autophagy receptors such as p62/SQSTM1 or NBR1 are rapidly and selectively targeted to lysosomal degradation by sorting in MVEs in starved cells, which may be a prerequisite to achieve a maximal bulk macroautophagy flux .…”
Section: Similarities Between Degradative and Secretory Mvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its role as a receptor for selective autophagy, p62 also localizes to cargos that will be degraded during the process, such as ubiquitin‐positive protein aggregates , damaged mitochondria, and invading bacteria . Under certain circumstances p62 can also be degraded by the proteasome or endosomal‐related autophagy , but it is primarily degraded during selective autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Third, it remains possible that some microautophagy pathways utilize only part of the core autophagy machinery. Importantly, ESCRT proteins are required for many types of microautophagy (Sahu et al, 2011;Liu et al, 2015;Oku et al, 2017;Tsuji et al, 2017;Mejlvang et al, 2018). While the topological equivalence of microautophagy and other ESCRT-dependent processes is compelling, a direct involvement of ESCRT machinery in microautophagy has been difficult to demonstrate.…”
Section: Introductionmentioning
confidence: 99%